La respuesta de la justicia constitucional frente a la obligación de los medios en la consolidación del estado democrático moderno. Nuevos caminos y nuevos desafíos - Borea Odría, Alberto (2011)
Modern democracy requires the power influencing the constitution of the political society be controlled democratically and help the system to be perpetuated with due guarantees of its citizens’ freedoms. With the development of communications technology, radio and television, which use bandwidth that is a natural resource belonging to the state, has acquired a relevant role in political life. People and parties that nominally have rights to participate in public elections and public service, may be blocked from establishing such a relationship with the electorate. Their message may be distorted by those running the programmes or owning the broadcasting concessions. Modern democracy must find remedies to avoid this from happening. Otherwise people’s right to choose is undermined and media owners become like goalkeepers of the democratic system, able to reserve rights of admission to their own. This article proposes specific solutions so that the rights to operate a concession are made compatible with guaranteeing that citizens are not deprived of their right to be apprised of all the alternatives and that political actors are not denied the right to participate in the process with a minimum level of equality. It must review the way that constitutional justice has responded to previous proposals to ensure that the conflict between private ownership and a democratic public service is correctly addressed.